When pricing treatment, know your costs and set your profit margins. Issue 22 (3rd June 2019) - Knopf, Alison
Abstract : Billing, ethics and parity have been hot‐button issues for substance use disorder (SUD) treatment centers for years, but the National Association of Addiction Treatment Providers (NAATP) is getting closer to finding solutions. At its annual leadership meeting in Washington last month, members, not to be deterred by a surprise lawsuit on opening day from American Addiction Centers (see ADAW, May 20, https://onlinelibrary.wiley.com/doi/10.1002/adaw.32368 ), gathered to hear from experts on how to properly conduct billing in a dynamic new environment.